2008
DOI: 10.1080/17453670710015508
|View full text |Cite
|
Sign up to set email alerts
|

Opposite cortical fracture in high tibial osteotomy: lateral closing compared to the medial opening‐wedge technique

Abstract: Background and purpose The aim with high tibial valgus osteotomy (HTO) is to correct the mechanical axis in medial compartmental osteoarthritis of the knee. Loss of operative correction may threaten the long-term outcome. In both a lateral closing-wedge procedure and a medial opening-wedge procedure, the opposite cortex of the tibia is usually not osteotomized, leaving 1 cm of bone intact as fulcrum. A fracture of this cortex may, however, lead to loss of correction; this was examined in the present study.Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 18 publications
2
67
0
3
Order By: Relevance
“…By contrast, we found that the presence of a lateral cortical hinge fracture was not a risk factor for developing nonunion. Previous work reported that an intact lateral cortical hinge is important to provide stability and to prevent lateral displacement [22]. Furthermore, it has been suggested that instability resulting from a fracture of the lateral cortical hinge could lead to nonunion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, we found that the presence of a lateral cortical hinge fracture was not a risk factor for developing nonunion. Previous work reported that an intact lateral cortical hinge is important to provide stability and to prevent lateral displacement [22]. Furthermore, it has been suggested that instability resulting from a fracture of the lateral cortical hinge could lead to nonunion.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that can lead to problems in bone healing are loss of correction resulting from hardware failure [4,16,20] and lateral cortical hinge fracture [1,19,22]. In the past decade, new angle-stable fixation implants have made the medial open wedge HTO technique more popular as a result of the higher loading capacity and the high residual stability after failure of the lateral cortex [1].…”
Section: Introductionmentioning
confidence: 99%
“…Although this event occurred in both groups (11 % in the xenograft and 8 % in the tricalcium phosphate groups), we found loss of correction with lateral cortical fracture only in the patients of the tricalcium phosphate group. Adequate strength of the construct can prevent the loss of correction, despite the onset of lateral cortical fracture [25].…”
Section: Discussionmentioning
confidence: 99%
“…In association with these concerns, weight bearing is usually allowed later than closing wedge osteotomies. In cases of deformities, greater than 10-15°lateral hinge rupture and loss of correction can occur [23]. Other disadvantages are slight tibial lengthening and low patella.…”
Section: Introductionmentioning
confidence: 99%